2015
DOI: 10.1016/j.cell.2015.02.024
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothalamic Agrp Neurons Drive Stereotypic Behaviors beyond Feeding

Abstract: SUMMARY The nervous system evolved to coordinate flexible goal-directed behaviors by integrating interoceptive and sensory information. Hypothalamic Agrp neurons are known to be crucial for feeding behavior. Here, however, we show that these neurons also orchestrate other complex behaviors in adult mice. Activation of Agrp neurons in the absence of food triggers foraging and repetitive behaviors, which are reverted by food consumption. These stereotypic behaviors that are triggered by Agrp neurons are coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
158
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(170 citation statements)
references
References 63 publications
(62 reference statements)
12
158
0
Order By: Relevance
“…Remarkably, initiating an identical AgRP photostimulation protocol in the home cage, prior to entering the shock-containing arena, drove fed mice to subsequently engage in this sensory discrimination task. This observation expands the set of complex motivated behaviors orchestrated by this remarkably small neuronal population [67, 14]. Thus, our findings provide a useful starting point for the investigation of neural circuits downstream of AgRP neurons, which are likely regulated by competing drives, including food seeking and threat avoidance.…”
Section: Discussionmentioning
confidence: 55%
“…Remarkably, initiating an identical AgRP photostimulation protocol in the home cage, prior to entering the shock-containing arena, drove fed mice to subsequently engage in this sensory discrimination task. This observation expands the set of complex motivated behaviors orchestrated by this remarkably small neuronal population [67, 14]. Thus, our findings provide a useful starting point for the investigation of neural circuits downstream of AgRP neurons, which are likely regulated by competing drives, including food seeking and threat avoidance.…”
Section: Discussionmentioning
confidence: 55%
“…By combining ARC AgRP targeted DREADDs with existing KO mouse models, follow-up studies revealed that NPY or GABA was necessary for the acute effects on ARC AgRP neuron activation, while AgRP was sufficient for long-term effects (Krashes et al 2013). More recent experiments have used hCh2R and DREADDs to further define how ARC AgRP neurons encode a negative balance signal for energy depletion (Betley et al 2015) and how they evoke typified energy seeking behaviors even in the absence of food (Dietrich et al 2015). Together, these studies establish a critical role of AgRP neurons in the regulation of feeding behavior and serve as a model by which to study the role of other genetically defined populations.…”
Section: Analysis Of α-Msh Action In the Cns Using Optogenetics And Cmentioning
confidence: 99%
“…Dietrich et al [214] recently used a chemogenetic approach to demonstrate that activation of AgRP neurons in the absence of food triggers foraging and repetitive behaviors, which are reverted by food consumption. These stereotypic behaviors are coupled with an increased willingness to explore normally fear- or anxiety-provoking environments.…”
Section: Role In Energy Expenditurementioning
confidence: 99%
“…These stereotypic behaviors are coupled with an increased willingness to explore normally fear- or anxiety-provoking environments. These effects are most likely not due to altered melanocortin signaling, since NPY5 receptor signaling is necessary to mediate the repetitive behaviors after AgRP neuron activation [214]. As previously described, inhibiting AgRP activity provides a way to rapidly halt the energy-intensive activity of foraging when food is found [73] .…”
Section: Role In Energy Expenditurementioning
confidence: 99%